Identification And Prevalence Rate Of Tuberculosis Among Patient With Diabetes Mellitus At PIMS Hospital Islamabad Pakistan (Journal of Pharmaceutical Negative Results, 2023)
The worldwide study suggested that Tuberculosis (TB) is one of the most common endemic ailments having the great causing factor of mortality and morbidity. As compare to general population the Diabetes Mellitus (DM patient has high risk factor for getting Tuberculosis (TB).The main purpose of the current research is to investigate the frequency rate of Tuberculosis among Patient with Diabetes Mellitus at PIMS Hospital Islamabad Pakistan from April, 2021 to July, 2021.in the current study the patient was examined from the age of 20 to 60 which is already treated for Diabetes Mellitus as well. The patient was asking for the sign and symptoms of Tuberculosis (TB). When the Tuberculosis (TB) sign and symptoms found positive than after that Sputum analysis were done. There are three Sputum sample (morning-spot) were collected to examine AFB. For Statiscal Data analysis we Used SPSS version 20. A total of 412 patients were included in the study. The mean age of the patients was found as 45.63 ± 10.33 years. Among these, 240 patients (59.3%) were female. Also 112 patients (21.7%) had type 1 DM while 247 (78.3%) had type 2 DM. When asked about the TB symptoms, they were positive in 51 patients (11.0%) while negative in remaining 381 patients (89%). However, further sputum analysis showed confirmed TB in 22 patients (4.1%) only. After adjustment of confounding factors, age, gender and type of DM were not found having significant role for development of TB among these patients. From the current research we conclude that there is high prevalence rate in Tuberculosis (TB) among diabetics Patient which is the main causing factor of mortality and morbidity in Pakistan and globally as well .